The Effect of Speech Therapy on Aphasia Levels in Non-Hemorrhagic Stroke Patients in the Seruni Room of Rsud Hajjah Andi Depu - Abdullah, M Syikir; Megawaty, Irna; Yetry, Yetry; Dewi, Triwulansari (Yayasan Inspirasi El Burhani, 2025)
Introduction: Non-hemorrhagic stroke is a brain disorder caused by the cessation or blockage of blood flow to the brain. Aphasia is a disorder in language function that arises from brain injury. Speech therapy is a rehabilitation process for people with communication disorders, so that they can interact more effectively. The use of the AIUEO method in therapy can help improve pronunciation, so that it is more easily understood by others by moving the tongue, lips, and facial muscles. Objective: This study aims to determine the effect of speech therapy on the level of aphasia in patients who have non-hemorrhagic stroke in the Seruni Room of RSUD Hajjah Andi Depu. Method: This research design is quantitative with a pre-experimental approach. The method used is one group pretest-posttest design. Results: The results of statistical analysis using the Wilcoxon Signed Ranks Test with the help of SPSS showed a significant value (2-tailed) of 0.004. This means (p<0.05), so that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected. Thus, there is a positive effect of speech therapy on the level of aphasia in non-hemorrhagic stroke patients in the Seruni Room of RSUD Hajjah Andi Depu. Conclusion: A 2024 study at Hajjah Andi Depu Hospital found that speech therapy significantly improved aphasia in non-hemorrhagic stroke patients. Patients' aphasia scores significantly improved after speech therapy (p < 0.05).